Could late measurement of serum creatinine be missed for patients without early increase in serum creatinine following coronary angiography?. Issue 50 (December 2017) - Liu, Yong; Duan, Chong-yang; Wang, Kun; Bei, Wei-jie; Guo, Xiao-sheng; Li, Hua-long; Wang, Ying; Chen, Shi-qun; Xian, Ying; Chen, Ping-yan; Geng, Qing-shan; Tan, Ning; et al.
Abstract : Abstract: Most patients are discharged early (within 24 hours) after coronary angiography (CAG) and may miss identification the late (24–48 hours) increase in serum creatinine (SCr), whose characteristics and prognosis have been less intensively investigated. We prospectively recruited 3065 consecutive patients with SCr measurement, including only1344 patients with twice SCr measurement (both early and late). The late contrast-induced acute kidney injury (CI-AKI) was defined as significantly increase in SCr (≥0.3 mg/dL or ≥50%) not in early phase, but only in late phase after the procedure, and the early CI-AKI experienced a significantly increase in early phase. Overall, CI-AKI developed in 134 patients (10%), and the incidence of late and early CI-AKI were 3.6% and 6.4%, respectively. There were no difference in age, renal, and heart function, contrast volume among patients with late and early CI-AKI. With mean follow-up period of 2.45 years, long-term mortality (3 years, 29.7% and 35.6%, respectively, P = .553) was similar for patients with late and early CI-AKI. Cox analysis showed that both late (adjusted HR 2.05; 95% CI, 1.02–4.15) and early (adjusted HR 2.68; 95% CI, 1.57–4.59) CI-AKI was significantly associated with long-term mortality (all P < .001). Only late increase in SCr, as late CI-AKI, accounted for about one-third of CI-AKI incidence and has similar good predictive value for long-term mortality with that of an early increase, early CI-AKI, among patients with SCr measured twice, supporting the importance of late repeating SCr measurement after CAG, even without an early significant increase in SCr. Abstract : Supplemental Digital Content is available in the text